Decomposed: a political ecology of music. Issue 3 (8th September 2015) - Devine, Kyle
Abstract This article is about what recordings are made of, and about what happens to those recordings when they are disposed of. It inscribes a history of recorded music in three main materials: shellac, plastic and data. These materials constitute the five most prevalent recording formats since 1900: 78s, LPs, cassettes, CDs and MP3s. The goal is to forge a political ecology of the evolving relationship between popular music and sound technology, which accounts not only for human production and consumption but also material manufacture and disposal. Such an orientation is useful for developing an analytical framework that is adequate to the complexities of the global material–cultural flows in which the recorded music commodity is constituted and deconstituted. It also strives towards a more responsible way of thinking about the relationship between popular music's cultural and economic value, on the one hand, and its environmental cost, on the other.